Sugar and dental caries - Romero-González, María Alejandra (2020)
Dental caries are caused by complex interactions that cause the demineralization of dental tissue, due to the presence of acids that are produced by cariogenic bacteria. The pain and infection caused by dental caries generate functional deterioration and decrease in quality of life. Caries are considered a global health problem that affects between 60% and 90% of the school population with a higher prevalence in children from low socioeconomic groups.The high consumption of free sugars has been implicated in the development of chronic non-communicable diseases, including obesity, cardiovascular diseases, diabetes mellitus type 2 and dental caries. It is for this reason, that the World Health Organization (WHO), in 2015, recommended reducing the intake of free sugars to less than 10% of total energy intake and preferably below 5%, both in adults as in children. Therefore, an early orientation to parents in the dental consultation about the consumption of free sugars would have the potential to benefit both oral health and general health.The purpose of this article is to review the current literature related to the consumption of sugar and dental caries.